Applying Grounded Theory - Barney G. Glaser (Grounded Theory Review: An International Journal, 2014)
Application of grounded theory (GT) is a relatively neglected topic by my colleagues. I have written several chapters in my books on applying GT. Two colleagues, Odis Simmons and Barbara Artinian (2009), as well as Dirks and Mills (2011), and Walsh (2014), have also written about applying GT. In the first two chapters of this book I discuss at length properties of generally applying GT and then professional issues and personal matters when applying of GT. There follows in this book nine chapters, four by me and one by Simmons and one by Artinian and one by Dirks and Mills, that are already published in books on GT, and one by Walsh. Thus, this book ends like a reader which publishes in one place already written work. The reader of this book may experience some redundancy in these chapters, but that is the nature of reader texts as different authors discuss the same ideas and topics.